Gestão de organizações artísticas: panorama e perspectiva para a produção acadêmica (Management and Connections Journal, 2021)
Art-driven organizations create, promote and distribute artistic practices throughout experiences. In the last four decades, the field of research on the management of art-driven organizations has gained strength and interest. Although the practice of managing art-driven organizations has occurred since the beginning of civilizations, research on their management practices and singularities is recent, reduced and dispersed. The purpose of this article is to integrate, systematize and consolidate academic production on the management of art-driven organizations. The research results provide an overview of academic research, structuring research singularities, themes and challenges. A challenge that stands out is the integration of organizational aesthetics as a promising perspective for the advancement of future research on art-driven organizations and their management practices. The main contribution of this research is the inauguration, in Brazil, of a review of academic production on the management of artistic organizations, highlighting its singularities, management practices and a renewing perspective to guide academic production.